Therapeutic effect on Alveolar echinococcosis by targeting EM-Leucine aminopeptidase - Zhou, Zhen; Zhou, Pei; Mu, Yalin; Wang, Lei; Cao, Zhenjin; Dong, Shizhong; Bao, Haihua; Yang, Baoliang; Xin, Minyuan; Li, Runle; Ge, Ri-Li; Tang, Feng (Frontiers in Immunology, 2022)
Alveolar echinococcosis (AE) is a parasitic disease caused by E. multilocularis metacestodes and it is highly prevalent in the northern hemisphere. We have previously found that vaccination with E. multilocularis Leucine aminopeptidase (EM-LAP) induced specific immune response and had an inhibiting effect on the parasites. In this study, the therapeutic effect of recombinant EM-LAP (rEM-LAP) on AE was evaluated and verified using Ubenimex, a broad-spectrum inhibitor of LAP. The results reveal that rEM-LAP could inhibit cyst growth and invasion and induce specific immunity response in BALB/c mice infected with E. multilocularis protoscoleces. The ultrasonic, MRI, and morphological results show that treatment with rEM-LAP inhibits E. multilocularis infection and reduces cyst weight, number, fibrosis and invasion. The same effect is observed for the treatment with Ubenimex by inhibiting LAP activity. The indirect ELISA shows that rEM-LAP could induce specific immunity response and produce high levels of IgG, IgG1, IgG2a, IgM, and IgA, and the serum levels of IFN-γ and IL-4 are significantly increased compared to the control groups, indicating that treatment with rEM-LAP leads to a Th1 and Th2 mixed-type immune response. This study suggests that EM-LAP could be a potential therapeutic target of E. multilocularis infection.